Enhanced Sound Capture System for Small Devices - Mihov, Slavy; Gleghorn, Tyler; Tashev, Ivan (Proceedings of XLIII International Scientific Conference on Information, Communication, and Energy Systems and Technologies ICEST 2008, 2008)
With mass propagation of the cellular phones and other small form factor devices as PDAs and other handhelds their usage in noise adverse environment is substantially increased. With adoption of the 3G and 4G wireless technologies the transition to videophone mode of communication is imminent. In addition most of the modern mobile phones have integrated cameras and are able to record short videos. In all these cases we have worse quality of the captured sound due to the old paradigm of a single microphone, which is supposed to be positioned close to the mouth of the human speaker. In this paper we propose enhanced sound capturing system for mobile devices. It consists of two directional microphones, pointing in opposite directions. Using a novel approach for the beamformer design we achieve satisfactory sound quality levels. The system output improves the perceptual sound quality with 0.29 MOS points and the SNR with 15 dB.